Corneal Biomechanics Differences Between Chinese and Caucasian Healthy Subjects - Vinciguerra, Riccardo; Herber, Robert; Wang, Yan; Zhang, Fengju; Zhou, Xingtao; Bai, Ji; Yu, Keming; Chen, Shihao; Fang, Xuejun; Raiskup, Frederik; Vinciguerra, Paolo (Frontiers in Medicine, 2022)
Purpose: The aim of this study was to assess the difference between Caucasian and Chinese healthy subjects with regards to Corvis ST dynamic corneal response parameters (DCRs). Methods: Two thousand eight hundred and eighty-nine healthy Caucasian and Chinese patients were included in this multicenter retrospective study. Subsequently, Chinese eyes were matched to Caucasians by age, intraocular pressure (IOP), and Corneal Thickness (CCT) using a case-control matching algorithm. The DCRs assessed were Deformation Amplitude Deformation Amplitude (DA) Applanation 1 velocity (A1v), integrated radius (1/R), deformation amplitude ratio (DAratio), stiffness parameter at applanation 1 (SPA1), ARTh (Ambrósio's Relational Thickness to the horizontal profile), and the novel Stress Strain Index (SSI). Results: After age-, CCT- and IOP- matching, 503 Chinese were assigned to 452 Caucasians participants. Statistical analysis showed a statistical significant difference between Chinese and Caucasian Healthy subjects in the values of SPA1 ( p=0.008), Arth (p=0.008) and SSI (p<0.001). Conversely, DA (p=0.674), A1v (p=0.373), DAratio (p=0.656) and 1/R (p=0.184) were not significantly different between the two ethnical groups. Conclusion: In conclusion we found significant differences in the values of the DCRs provided by the Corvis ST between Chinese and Caucasian healthy subjects.